Perbandingan Sintesis Antara Senyawa 2'-Nitrokhalkon dan 2,4-Dimetoksi-2'-Nitrokhalkon dengan Bantuan Iradiasi Gelombang Mikro - Putri, Navyanti Firda; Soewandi, Ami; Budiati, Tutuk (Jurnal Farmasi Sains dan Terapan, 2019)
The purposes of this research were to find out the influence of a methoxy group to the result percentage reaction and synthesize derivatives of chalcone from derivatives of acetophenone and 2-nitrobenzaldehyde. The purity analysis of the synthesized result was determined by melting point assay and thin layer chromatography, while the identification of the structure was determined by spectrophotometry, infrared pectrophotometry and nuclear magnetic resonance (H-NMR). In the synthesis of compounds formed 3-hydroxy-3- (2-nitrophenyl)-1-fenilpropan-1one and 3-hydroxy-1-(2,4-dimetoksifenil)propan-1-on. The synthesis results obtained an average percentage yield synthesis of 3-hydroxy-3-(2-nitrophenyl)-1-phenylpropan-1-on with the conventional method and with the aid of microwave irradiation amounted to 60.45% and 32.36%. The percentage results of the synthesis for compounds 3-hydroxy-1-(2,4-dimethoxyphenyl)-3-(2-nitrophenyl)propan-1-on with the conventional method and with the aid of microwave irradiation amounted to 11.51% and 5.57%. The influence of methoxy groups can decrease the reactivity of acetophenone.